Cross-cultural challenges and adjustments of expatriates: a case study in Malaysia - Mohd Tahir, Aida Hafitah; Ismail, Maimunah (Center for International Conflict Resolution, Yalova University, 2007)
Due to globalization and vision to be an industrialized nation, Malaysia acknowledges the inflow of expatriates into the country to meet the demands for skilled and professional manpower. This paper reports on a study conducted among a group of expatriates in Malaysia. The objectives of the study are to examine challenges faced by the expatriates and adjustments made to the challenges. Cultural clashes between foreign and local values are inevitable in which expatriates experience challenges. Indepth interviews were conducted with 20 male and female expatriates working in various firms and institutions in Malaysia. The study highlighted the psychological, socio-cultural and work challenges. Adjustments were based on individual initiatives based on the psychological and mental strengths of the expatriates, combined with efforts of peer expatriates, parent firms and host organizations.